Cross-border copyright licensing : law and practice - Lavizzari, Carlo Scollo; Viljoen, René, 1944- (Elgar intellectual property law and practice, 2018)
In today's legal environment, copyright licensing requires an international perspective. Licensors in both emerging and developed markets must have a detailed understanding of cross-border practices. Cross-Border Copyright Licensing provides a select guide to copyright licensing practices in a number of jurisdictions, addressing key cross-border considerations. Key features include: ; chapter by chapter analysis of licensing legislation in the most frequently encountered jurisdictions including: China, the EU, India, Mexico, Russia, Singapore, South Africa and the USA ; discussion of the inter-relation between copyright licensing and competition law ; clear delineation of the most relevant and critical legal issues relating to licensing practice across the named jurisdictions allowing for ease of reference ; contributions from expert practitioners with invaluable first hand knowledge of international licensing practices. This book will prove a valuable resource for lawyers who are implementing or enforcing a copyright licensing scheme, acting as a first point of reference on cross-border issues. Scholars of Intellectual Property will also find the text to be a useful guide on international regulations and practices.